Therapeutic singing and expiratory muscle strength training in Parkinson's disease: a mixed methods comparison - Brown, Jessy; Stegemöller, Elizabeth L. (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe purpose of this study was to understand how two respiratory strengthening protocols, therapeutic singing (TS) and expiratory muscle strength training (EMST), compare on measures of quality of life (QOL), depression and anxiety for persons with Parkinson's disease. An equally important aim was to understand participants' perceptions of both treatments.MethodsQuantitative and qualitative datasets were integrated in a convergent mixed methods design within a randomized crossover intervention trial. Thirteen persons with mild-moderate PD (Hoehn and Yahr stage 1–3) completed both interventions, in random order, for 4 weeks, 5 days per week, for approximately 20 min per day. Participants completed self-report questionnaires (Geriatric Depression Scale, Parkinson's Anxiety Scale, Parkinson's Disease Questionnaire-39, and a Survey after Treatment) after each intervention, and twelve participants' qualitative data were analyzed.ResultsQuantitative data did not reveal significant differences between the interventions in depression on the Geriatric Depression Scale or anxiety on the Parkinson's Anxiety Scale and the qualitative data support those findings. There were no significant differences between interventions in QOL as measured by the Parkinson's Disease Questionnaire-39, but there was a main effect of time, with a significant decline (p = 0.01) in perceived QOL between baseline and the final visit. The quantitative data diverged from the qualitative data as there were no themes that emerged to corroborate a decrease in QOL. Five qualitative themes were derived from thematic analysis: Benefits, Accessibility, Acceptability, Advice/Feedback, and Preference. Participants' perceptions of the interventions were closely aligned to individual differences and preferences, with an equal split of participants preferring TS and EMST.ConclusionsFindings from this mixed methods comparison of two respiratory interventions will help to improve the acceptability and accessibility of the interventions to better facilitate adherence to the interventions and promote continued engagement, thereby delaying respiratory decline in those with PD.